2020
DOI: 10.1038/s41598-020-63841-8
|View full text |Cite
|
Sign up to set email alerts
|

The protein Deleted in Breast Cancer-1 (DBC1) regulates vascular response and formation of aortic dissection during Angiotensin II infusion

Abstract: Cardiovascular diseases are among the main causes of morbimortality in the adult population. Among them, hypertension is a leading cause for stroke, heart disease and kidney failure. Also, as a result of arterial wall weakness, hypertension can lead to the development of dissecting aortic aneurysms, a rare but often fatal condition if not readily treated. In this work, we investigated the role of DBC1 in the regulation of vascular function in an ANGII-induced hypertension mouse model. We found that WT and DBC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…While some interpret the effects of vasa vasorum removal, occlusion, or, otherwise, hypoperfused microvessels as proatherosclerotic events, others view these data of consequent vascular wall necrosis and disruption as indicative of aneurysm or dissection. One useful example is the recent work of Colman et al ( 133 ), who, while studying the role of deleted in breast cancer gene in angiotensin II (Ang-II)–infused hypertensive mice, made the somewhat unexpected observation of aortic delamination associated with extravasated red blood cells from adventitial vasa vasorum and intramural hematoma (IMH) formation. Current experimental models have not enabled sufficiently rigorous experimentation to determine whether vasa vasorum dysfunction is an aggravator as opposed to a consequence of lesion development in atherosclerotic disease.…”
Section: Introductionmentioning
confidence: 99%
“…While some interpret the effects of vasa vasorum removal, occlusion, or, otherwise, hypoperfused microvessels as proatherosclerotic events, others view these data of consequent vascular wall necrosis and disruption as indicative of aneurysm or dissection. One useful example is the recent work of Colman et al ( 133 ), who, while studying the role of deleted in breast cancer gene in angiotensin II (Ang-II)–infused hypertensive mice, made the somewhat unexpected observation of aortic delamination associated with extravasated red blood cells from adventitial vasa vasorum and intramural hematoma (IMH) formation. Current experimental models have not enabled sufficiently rigorous experimentation to determine whether vasa vasorum dysfunction is an aggravator as opposed to a consequence of lesion development in atherosclerotic disease.…”
Section: Introductionmentioning
confidence: 99%
“…DBC1 may affect senescence differently depending on the type of tissue or stimulus. For example, DBC1 deletion protects adipose tissues from senescence in obese mice [27]; yet, vascular smooth muscle cells in DBC1 knockout mice fail to proliferate with an increased expressions of MMPs in response to ANGII [48]; and we found that DBC1 suppressed senescence following DNA damage. DBC1 knockout mice have a shorter lifespan and an almost 2-fold higher tumorigenesis rate than wild-types [37], implying the overall functions of DBC1 in vivo are favorable.…”
Section: Discussionmentioning
confidence: 66%
“…HEK293T cells were grown in DMEM (high-glucose), 10% FBS, 100 units/ml of penicillin, and 100 μg/ml of streptomycin. Cells were transfected with FLAG-SIRT6 plasmid (Addgene plasmid number 13817) with Lipofectamine 2000 (Thermo Fisher Scientific) for 48 h. Cells were later incubated with 10 μ m NO 2 -OA (or 10 μ m OA) in serum-free DMEM for 1 h. Cell lysis was performed as described previously ( 79 ). Briefly, cells were lysed in RIPA buffer (25 m m Tris, pH 8.0, 150 m m NaCl, 1% Nonidet P-40, 0.1% SDS) supplemented with 5 m m NaF, 50 m m 2-glycerophosphate, 1 μ m trichostatin A, 5 m m nicotinamide, and a protease inhibitor mixture (Roche).…”
Section: Methodsmentioning
confidence: 99%